The complete mitochondrial genome of the hybrid grouper (Cromileptes altivelis♀ × Epinephelus lanceolatus♂) with phylogenetic consideration - Chen, Jiaxing (Mitochondrial DNA B Resour, 2017)
The complete mitochondrial genome of the Hybrid grouper (Cromileptes altivelis♀ × Epinephelus lanceolatus♂) was presented in this study. The mitochondrial genome is 16,501 bp long and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. The gene order and composition of Hybrid grouper mitochondrial genome was similar to that of most other vertebrates. The nucleotide compositions of the light strand are 26.24% of A, 15.68% of C, 29.07% of T, and29.01% of G. With the exception of the NADH dehydrogenase subunit 6 (ND6) and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand. The phylogenetic analysis by maximum-likelihood (ML) method shows that the hybrid grouper has closer relationship to C. altivelis.